Achieving Grand Tour success: a pilot study using cycling`s World Tour points - Filipas, L.; La Torre, A.; Menaspà, P.; Giorgi, H. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: In cycling, the Union Cycliste International (UCI) World Tour points system provides a basis to assess the development of riders by longitudinally monitoring accumulated points. The main aim of the present analysis was to compare the annual aggregation of points of Grand Tours (GT) contenders during the years before and the year after achieving an overall top-ten (T10) placing in a GT for the first time. METHODS: Data from professional cyclists who achieved their first T10 general classification result in a GT between 2010 and 2015, inclusive, were included in the analysis. RESULTS: There were 43 cyclists who achieved a T10 placing for the first time between 2010 and 2015, with an average number of UCI points of 139.7±77.1 points. Of these cyclists, 20 placed within the top five (T5), and averaged 183.1±71.6 UCI points within the T5 season. There was a significant difference in the number of points accumulated in the T5/T10 between the T5 and T10 groups (P<0.05), however there were no significant differences between the groups in the other seasons. CONCLUSIONS: An apparent spike in the number of points obtained in the T5 or T10 season when compared to the preceding seasons may be due to successful riders being afforded more opportunities to play leading roles within the team. This effect may have persisted into the season following the T5/T10 finish.